2017
DOI: 10.1088/1748-9326/aa8a17
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the potential for industrial waste heat reutilization in urban district energy systems: method development and implementation in two Chinese provinces

Abstract: Utilizing low-grade waste heat from industries to heat and cool homes and businesses through fourth generation district energy systems (DES) is a novel strategy to reduce energy use. This paper develops a generalizable methodology to estimate the energy saving potential for heating/cooling in 20 cities in two Chinese provinces, representing cold winter and hot summer regions respectively. We also conduct a life-cycle analysis of the new infrastructure required for energy exchange in DES. Results show that heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These cross-infrastructure strategies enabled by district energy systems that use waste heat as well as bio-resources can be an important decarbonization strategy that is further enhanced by CUD. Recent studies of more than 600 Chinese cities have indicated that cross-infrastructure efficiency strategies, such as using low-grade waste heat in district energy systems and exchanging waste materials (fly ash to cement, steel slag to cement), can contribute to as much as two-thirds of single-sector efficiency strategies established by the Chinese national government (Ramaswami et al 2017;Tong et al 2017). Each city, based on its mix and structure of industrial, commercial, and residential activities, will show different potential for implementing cross-infrastructure solutions.…”
Section: Lever 3: Cross-infrastructure Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These cross-infrastructure strategies enabled by district energy systems that use waste heat as well as bio-resources can be an important decarbonization strategy that is further enhanced by CUD. Recent studies of more than 600 Chinese cities have indicated that cross-infrastructure efficiency strategies, such as using low-grade waste heat in district energy systems and exchanging waste materials (fly ash to cement, steel slag to cement), can contribute to as much as two-thirds of single-sector efficiency strategies established by the Chinese national government (Ramaswami et al 2017;Tong et al 2017). Each city, based on its mix and structure of industrial, commercial, and residential activities, will show different potential for implementing cross-infrastructure solutions.…”
Section: Lever 3: Cross-infrastructure Strategiesmentioning
confidence: 99%
“…Each city, based on its mix and structure of industrial, commercial, and residential activities, will show different potential for implementing cross-infrastructure solutions. Thus, algorithms that can estimate the potential of these cross-infrastructure strategies should be customized to each city (Tong et al 2017).…”
Section: Lever 3: Cross-infrastructure Strategiesmentioning
confidence: 99%
“…New, fourth-generation district energy systems (DESs), which have been demonstrated to be both economically and technically feasible, 28 directly utilize low-grade waste-heat ( T < 100 °C) for reapplication toward heating (through district heating systems (DHSs)) and cooling (by evaporative processes). 29 , 30 Such novel, multisector strategies have been less studied to date but may offer additional benefits to conventional, single-sector strategies. 26 , 31 , 32 Organic Rankine cycles (ORCs) that utilize low- and medium-grade (100–400 °C) waste-heat to generate electricity also offer waste-heat reuse potential.…”
Section: Introductionmentioning
confidence: 99%
“…There is high interest in circular economy strategies in Indiaincluding offsetting residential and commercial heating and cooling emissions, but their impact is yet to be quantified. New, fourth-generation district energy systems (DESs), which have been demonstrated to be both economically and technically feasible, directly utilize low-grade waste-heat ( T < 100 °C) for reapplication toward heating (through district heating systems (DHSs)) and cooling (by evaporative processes). , Such novel, multisector strategies have been less studied to date but may offer additional benefits to conventional, single-sector strategies. ,, Organic Rankine cycles (ORCs) that utilize low- and medium-grade (100–400 °C) waste-heat to generate electricity also offer waste-heat reuse potential. ORCs operate similarly to a traditional steam Rankine cycle except that they use an organic working fluid instead of steam.…”
Section: Introductionmentioning
confidence: 99%
“…For the projects examined, the variety in size and technologies is wide, ranging from microscale projects of about 0,5-1 GWh/year (Brückner et al, 2014) to metropolitan projects of several PJ/year (Dou et al, 2018, Kim et al 2018, Tong et al, 2017, see Table S1). The extension of networks connecting industrial sources to DH substations or users also varies from a few hundred meters (Dominkovic et al, 2017) up to some 50 km (Sandvall et al, 2016).…”
Section: Introductionmentioning
confidence: 99%